1988
DOI: 10.1254/jjp.46.1
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the development of analgesic tolerance to morphine by concurrent treatment with opioid-but not non-opioid-mediated stress in mice.

Abstract: Abstract-Studies have been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The results suggest that FS and PSY-stress differentially act on the spinal cord, and that x-opioid receptor mechanisms are mainly in volved in the suppression by PSY-stress. This may be supported by our earlier findings (10,20) that an application of PSY-stress produces analgesia through the mediation of x-opioid receptors, whereas FS-stress produces analge sia by different opioid receptor mechanisms, i.e., through the mediation of ,u-opioid recep tors.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The results suggest that FS and PSY-stress differentially act on the spinal cord, and that x-opioid receptor mechanisms are mainly in volved in the suppression by PSY-stress. This may be supported by our earlier findings (10,20) that an application of PSY-stress produces analgesia through the mediation of x-opioid receptors, whereas FS-stress produces analge sia by different opioid receptor mechanisms, i.e., through the mediation of ,u-opioid recep tors.…”
Section: Discussionsupporting
confidence: 71%
“…However, since it has been reported that pretreatment with reserpine abo lished the analgesic effect of morphine given i.c.v. (17), and likewise, the analgesic effect induced by FS and PSY-stress exposure is not recognized in reserpinized mice (10,13), the effect of exposure to stress on the supraspinal level could not be excluded. It is likely that the exposure to stress indirectly alters or modu lates the spinal function through the descend ing pathway and consequently suppresses the development of antinociceptive tolerance with out affecting the supraspinal morphine anti nociception and tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More over, the attenuation of pain resulted from anti-inflammatory effects (12) of or modula tion of SIA by glucocorticoids (3,4,13,14) released following FS-stress and may be unrelated to the suppression by FS-stress of the development of morphine tolerance. Indeed, FS-SIA per se did not affect mor phine analgesia on the 1st day, and low current FS (0.5 mA) which did not produce any appreciable analgesic effect suppressed the morphine tolerance as well (1).…”
Section: Discussionmentioning
confidence: 84%
“…In our previous experiments which were undertaken to examine the effect of the con current exposure to various stressful stimuli on the development of morphine tolerance in mice, we found that footshock (FS) stress, which produces analgesia through an opioid receptor, only blocked the development of morphine tolerance (1). Meanwhile, there are several reports which suggest that the analgesic actions induced by stress exposure have relevance to the endocrine mechanisms: namely, stimulation of the pituitary-adrenal axis (e.g., hypophysectomized rat attenuated analgesia following FS, cold water swimming and immobilization) (2); footshock stress induced analgesia was enhanced by adrenal ectomy in mice (3); and the analgesic effect induced by an opioid mediated stress such as FS-stress under certain conditions was sup pressed by the treatment with dexamethasone or by adrenalectomy (4).…”
mentioning
confidence: 99%